ASYMPTOTICS OF THE MULTICLUSTER WAVE FUNCTIONS IN THE BINAR STRONG BIND CHANNELS. 1. ELEMENTS OF THE FORMALISM - Afanas’eva, N.V.; Burkova, N.A.; Zhaksybekova К.А.; Kabytaev, Ch.Z. (Recent Contributions to Physics, 2008)
The mathematic formalism for the calculation of the asymptotic constants of the radial wave functions in the binary strong bind cluster channels constructed by projecting method is present.